Pemikiran Waleed el-Ansary tentang “A Common Word” dalam Perspektif Metafisika Perennial - Suhermanto Ja’far (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2012)
The discourse of “the Common Word” between you and us has initiated a series of seminars involving world religious institutions. Theological implications of the common words become a prevalent discussion. Fundamental questions that arise are: “When both Islam and Christianity claim to have received the revelation of God, then what does that mean that the word of God has become a book? Or transformed into the image of Jesus? “However, it does not mean that such matters can simply be brought into the realm of theological studies because it will lead to a polemic and highlight the differences rather than the pure spirit of faith. Theology will only hold us to understand the main doctrines that had been circling around each religious tradition. Therefore, this article, which explores the idea of Waleed el-Ansary, is presented as an effort to understand the “Word of God” within Islam’s and Christianity’s perspective. Hence, as religious people, we all get the meaningfulness of life or even salvation.